(untitled) (Research, Society and Development, 2021)
Objective: to analyze the scientific evidences about adverse events occurred in surgical patients. Method: integrative literature review, with data collection from September to October 2020, in three databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Nursing Database (BDENF). Primary articles were selected, published in Portuguese, English and Spanish, without temporal cutout. Results: 18 articles were eligible; 44,4% (n=8) were conducted in Brazil. The study sample ranged from 19 to 11.499 medical records, with incidence/prevalence of 3,5% to 21,8%, and estimated mortality rate of 1,82% to 18,4%. The prevention of events ranged from 7,7% for cases related to medication to 90% for general events. Events associated with infection and medication/intravenous fluids were prevalent. Not following the norms, failure in technical skills, overconfidence and distractions were contributed factors to the occurrence of adverse events. Conclusion: the quality and safety of care need to be improved in perioperative care units, mainly in cases of infection and adverse drug events.